SCHWANNOMA OF SCAPULA: CASE REPORT AND LITERATURE REVIEW - Stevanović, Stefan; Petrović , Jovica; Milićević , Aleksandar; Petrović , Jelena; Đorđević , Nikola; Nikolić , Aleksandra (Sanamed, 2024)
Introduction: Schwannomas are benign peripheral nerve tumors, more often localized in soft tissues than bones. Out of about 200 recorded cases of schwannoma of bone, only three cases of schwannoma of scapula have been described to date.Case report: We present the case of a 73-year-old female patient with an asymptomatic schwannoma of the scapula. Physical examination revealed a solid, fixed, well-defined walnut-size tumefaction in the right scapula area. CT of the chest confirmed a 2.33 x 0.96 cm diameter tumor at the junction of the upper-third and middle-third of the medial border of the right scapula. After discussion with the patient, it was decided to proceed with surgical removal of the tumor. The surgery involved partial resection of the tumor-affected part of the scapula. Histopathological examination confirmed it was a schwannoma of bone. No clinical or radiological signs of disease recurrence were observed during the one-year follow-up.Conclusion: Schwannomas of bone are rare, slow-growing tumors. A definitive diagnosis is made based on histopathological and immunohistochemical findings. The main treatment modalities include curettage or “en bloc” resection. Recurrence is rare.
Keywords: neurilemmoma; tumor; surgical treatment; histopathology; radiology